2016
DOI: 10.4103/1735-1995.179887
|View full text |Cite
|
Sign up to set email alerts
|

Is type 2 diabetes mellitus in mechanically ventilated adult trauma patients potentially related to the occurrence of ventilator-associated pneumonia?

Abstract: Background:Ventilator-associated pneumonia (VAP) is a type of lung infection that typically affects critically ill patients undergoing mechanical ventilation (MV) in the intensive care unit (ICU). Patients with type 2 diabetes mellitus (T2DM) are considered to be more susceptible to several types of infections including community-acquired pneumonia. However, it is not clear whether T2DM is a risk factor for the development of VAP. The purpose of this study was to determine the risk of VAP for diabetic and nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The reported prevalence rate regarding DM varies around the world. Various studies have estimated the number of people with DM worldwide from 451 million in 2017 to 592 million in 2035 ( 22 23 ). Type 1 DM can occur at any age, but its highest incidence is at birth to age 14 ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported prevalence rate regarding DM varies around the world. Various studies have estimated the number of people with DM worldwide from 451 million in 2017 to 592 million in 2035 ( 22 23 ). Type 1 DM can occur at any age, but its highest incidence is at birth to age 14 ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors play an important role in transforming a brief autoimmunity into type 1 DM. Improvement of living standards and reduction of exposure to microorganisms are likely to result in rise of autoimmunity ( 23 , 25 ). Type 2 DM has a slow onset, and unlike type 1, its common symptoms lack any kind of acute metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we showed that VAP increased the OR of dying in both men and women with T2DM. Previous studies also reported that T2DM is associated with increased mortality rates in VAP patients [ 38 , 39 ]. The several factors that could explain the higher rates of mortality in T2DM patients with VAP include older age and more frequent comorbidity, which increase vulnerability to severe complications, such as organ failure, and lead to earlier and more frequent death [ 31 ].…”
Section: Discussionmentioning
confidence: 83%
“…Unmodifiable risk factors that predispose trauma patients to pneumonia can be considered in terms of patient factors and injury factors (Table 1). Patient factors that are independent risk factors for the development of pneumonia among trauma patients include increasing age [11, 12, 13•], male gender [12], cardiac disease [12], COPD [1,11], type II diabetes mellitus [14], cancer [12], and immunosuppression [1]. There are multiple injury factors that increase risk for pneumonia.…”
Section: Risk Factors and Prevention Unmodifiable Risk Factorsmentioning
confidence: 99%